Work Motivation as a Central Determinant of Teacher Performance: An Integrated Structural Model of Leadership Style, Organizational Culture, and Compensation - Nurul Fatihah; Sarwo Edy Handoyo; Juanda (Al-Qalam Institue, 2026)
This study aims to examine the effects of compensation and work motivation on teacher performance by integrating leadership style, organizational culture, compensation, and work motivation into a single structural model. The research employs a causal associative quantitative approach using a survey method with a 1–5 Likert scale questionnaire administered to 94 teachers. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that compensation significantly influences work motivation, and work motivation significantly affects teacher performance. However, work motivation does not mediate the relationship between compensation and teacher performance. Leadership style primarily affects teacher performance indirectly through its influence on motivation rather than through a direct effect. Compensation directly enhances motivation and contributes significantly to teacher performance, while organizational culture shows an indirect but statistically insignificant effect. These results imply that strengthening teacher performance requires strategic emphasis on enhancing work motivation through effective leadership and supportive compensation systems. Educational institutions should prioritize leadership practices and fair compensation policies to foster sustainable performance improvement.